Shallow water phytoplankton responses to nitrate and salinity enrichment may be modified by benthic processes. Issue 1 (2nd January 2020) - McGowan, Suzanne; Leavitt, Peter R.; Barker, Tom; Moss, Brian
ABSTRACT: The effects of salinity (as chloride [Cl] at 600, 1000, 1600, and 2500 mg L −1 ) and nitrate (as nitrogen [N] loading rates using concentrations of 1, 2, 5, and 10 mg L −1 ) additions on phytoplankton communities (as chlorophyll and carotenoid pigments) were determined using a fully factorial 3 m 3 mesocosm pond experiment. Redundancy analysis followed by variance partitioning analysis (VPA) statistically compared phytoplankton with water chemistry, zooplankton, phytobenthos (aquatic plants and periphyton), and zoobenthos to understand relationships among benthic and pelagic components. Repeated measures analysis of variance (RM-ANOVA) indicated no interactive effects of the 2 treatments. In VPA, physicochemical variables explained the most variance (33.6%) in the phytoplankton pigment dataset relative to benthic primary producers (0.4%) and invertebrates (2.3%). Salinisation led to an increase in biomass of planktonic siliceous algae (Cl ≥1600 mg L −1 ) and chlorophytes and cyanobacteria (Cl ≥2500 mg L −1 ), which we infer was caused by increased phosphorus release from sediments while aquatic plants and periphyton declined. Nitrate additions increased the biomass of cryptophytes and chlorophytes at intermediate N loading rates using concentrations of 5 mg L −1 (associated with greater ammonium [NH4 -N] availability and shifts in aquatic plant composition). These findings support the hypothesis that the relative availability of reduced versus oxidised N forms is an important driver of phytoplankton composition. Together, these results suggest that pelagic biota are highly sensitive to salinity and nitrate increases, and that the phytoplankton compositional shifts are driven by indirect effects on water chemistry (bioavailable P mobilisation, changes in N forms), which are mediated by benthic processes.